ICD Social Codes: An Underutilized Resource for Tracking Social Needs. Issue 9 (September 2017) - Torres, Jacqueline M.; Lawlor, John; Colvin, Jeffrey D.; Sills, Marion R.; Bettenhausen, Jessica L.; Davidson, Amber; Cutler, Gretchen J.; Hall, Matt; Gottlieb, Laura M.
Abstract : Background: Social determinants of health (SDH) data collected in health care settings could have important applications for clinical decision-making, population health strategies, and the design of performance-based incentives and penalties. One source for cataloging SDH data is the International Statistical Classification of Diseases and Related Health Problems (ICD). Objective: To explore how SDH are captured with ICD Ninth revision SDH V codes in a national inpatient discharge database. Materials and Methods: Data come from the 2013 Healthcare Cost and Utilization Project (HCUP) National Inpatient Sample, a national stratified sample of discharges from 4363 hospitals from 44 US states. We estimate the rate of ICD-9 SDH V code utilization overall and by patient demographics and payer categories. We additionally estimate the rate of SDH V code utilization for: (a) the 5 most common reasons for hospitalization; and (b) the 5 conditions with the highest rates of SDH V code utilization. Results: Fewer than 2% of overall discharges in the National Inpatient Sample were assigned an SDH V code. There were statistically significant differences in the rate of overall SDH V code utilization by age categories, race/ethnicity, sex, and payer (all P <0.001). Nevertheless, SDH V codes were assigned to <7% of discharges in any demographic or payer subgroup. SDH V code utilization was highest for major diagnostic categories related to mental health and alcohol/substance use-related discharges. Conclusions: SDH V codes are infrequently utilized in inpatient settings for discharges other than those related to mental health and alcohol/substance use. Utilization incentives will likely need to be developed to realize the potential benefits of cataloging SDH information. Abstract : Supplemental Digital Content is available in the text.